Characteristics of Charismatic Leaders and Their Impact on Work Culture - Yuli Umro'atin (Journal of Innovative Islamic Education Management, 2026)
Leadership plays a strategic role in shaping organizational work culture; however, not all leadership styles are capable of creating a strong and sustainable work culture. One common issue that often arises is the dependence of work culture on a leader’s figure without the institutionalization of clear values. Charismatic leadership is often considered effective, yet there is still debate regarding its impact on organizational work culture. Therefore, this study aims to analyze the characteristics of charismatic leaders and their impact on organizational work culture based on a literature review. This study employs a qualitative method using a library research approach. Data were collected through a review of books, scholarly journals, and relevant publications discussing charismatic leadership and work culture. Data analysis techniques included content analysis and qualitative descriptive analysis. The findings indicate that the characteristics of charismatic leaders such as a clear vision, moral integrity, inspirational communication, empathy, and emotional intelligence play a role in building trust and employees’ emotional attachment. This trust encourages the internalization of leadership values that shape a visionary and adaptive work culture. In conclusion, charismatic leadership has a significant influence on organizational work culture; however, it needs to be balanced with strong organizational systems to ensure the sustainable development of work culture.